KARAKTERISTIK BRIKET TONGKOL JAGUNG DAN BRIKET TEMPURUNG KELAPA BERDASARKAN VARIASI UKURAN BUTIRAN ARANG DAN KONSENTRASI PEREKAT - Hondong, Hasfiana; Ihsan, Ihsan; Hernawati, Hernawati (Universitas Islam Negeri Alauddin Makassar, 2017)
This study aims to investigate the influence of grain size and concentration of charcoal briquettes adhesive on the characteristics of the corn cob and coconut shell briquettes. In this study is made briquettes with a variety of different compositions. Based on the research that has been done, briquettes which has the highest density value of 0.82 g/cm3 with a grain size of 80 mesh with adhesive concentration 20 %, the highest water content of 0.42 % with a grain size of 80 mesh with adhesive concentration 20 %, the value of the highest heat briquettes corn cobs at 3747.294 cal/g with a grain size of 60 mesh with adhesive concentration 15 %, and the highest ash content of 0.16 %. As for the coconut shell briquettes have the highest density values of 1.05 g/cm3 with a grain size of 60 mesh with each adhesive 15 % and 20 %, the highest water content of 0.61 % with a grain size of 60 mesh with the concentration of adhesive 20 %, to a high of 3940.148 calorific value cal/g with a grain size of 40 mesh with adhesive concentration 10 %, and the highest ash content of 0.35 % with a 20 % concentration of adhesive.Keywords: Particle Size, Concentration Adhesives, Tapioca Starch, Shell Coconut and Corn Cob.